Fixing the women or fixing universities: Women in HE leadership - Paula Burkinshaw; Kate White (Administrative Sciences, 2017)
The lack of women in leadership across higher education has been problemitised in the literature. Often contemporary discourses promote 'fixing the women' as a solution. Consequently, interventions aimed at helping women break through 'the glass ceiling' abound. This article argues that the gendered power relations at play in universities stubbornly maintain entrenched inequalities whereby, regardless of measures implemented for and by women, the problem remains. The precariousness for women of leadership careers is explored through two separate but complementary case studies (from different continents and different generations) each one illuminating gender power relations at work. The article concludes by arguing that it is universities themselves that need fixing, not the women, and that women's growing resistance, particularly of the younger generation, reflects their dissatisfaction with higher education leadership communities of practice of masculinities.
Keywords: 350; women in higher education; gender and leadership; gendered power relations